Capacity building among frontline health workers (FHWs) in screening for cardiovascular diseases (CVDs): Findings of an implementation study from Bihar, India - Neeraj Agarwal; CM Singh; Bijaya Nanda Naik; Abhisek Mishra; Shamshad Ahmad; Pallavi Lohani; Saket Shekhar; Bijit Biswas (AIMS Press, 2023)
Background: Community-based screening is one of the key preventive strategies to tackle the ever-rising burden of non-communicable diseases (NCDs) under the National Programme for Prevention & Control of Cancer, Diabetes, Cardiovascular Diseases and Stroke (NPCDCS). Objective: The current study was aimed to build capacity among frontline health workers (FHWs) in screening for cardiovascular diseases (CVDs) under NPCDCS in the selected districts of Bihar state. Methodology: This was an implementation study with follow-up components, conducted among 75 FHWs [14 auxiliary nurse midwives (ANMs) and 61 accredited social health activists (ASHAs)] from 15 primary healthcare facilities across four districts of Bihar state from October 2019 to September 2021. The selected FHWs were initially trained on NPCDCS for a day, including pre- and post-training knowledge assessment. Then, supportive supervision (SS) visits using a predesigned questionnaire were done. Results: The pre- and post-training mean knowledge scores of the FHWs were 12.9 and 22.1, respectively, with an overall effect size of 2.5. During SS visits, only 20.0% of the visited primary healthcare facilities had all the required logistics to conduct weekly NCD screening clinics for CVDs. Considering different measurements and operative skill proficiencies of FHWs, waist circumference skills (41.7% for ANMs and 50.8% for ASHAs), followed by blood pressure (BP) (41.7%) and random blood sugar (RBS) measurement (25.0%), were found to be the most deficient skills (among ANMs). Moreover, the quality of initial and follow-up home visits was found to be satisfactory for only 54.1% of the ASHAs. The reported barriers of NCD screening were reported to be non-cooperation, unawareness among community dwellers, lack of knowledge and skill of FHWs, logistic constraints and delayed honorarium credit. Conclusion: One-day training on NCDs for FHWs was quite effective. However, for translating all the desired skills for CVD screening into action, periodic training needs assessment, and SS of FHWs might be fruitful.